Implementation of The Cambridge International Primary Programme on A Mosque-Based Learning Culture - Mukhlishah Mukhlishah; Ni'matus Sholihah (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2024)
Education is one solution to shape Indonesia into a developed country. Through education, quality and competent human resources can be produced. This naturally stems from designing a quality learning curriculum to foster a generation of high-caliber individuals for the nation. The quality of the international curriculum has gained global recognition and is complemented by teachings following the principles of Prophet Muhammad SAW, implemented through mosque-based learning. This research aims to describe the implementation of the Cambridge International Primary Program, which carries implications for mosque-based learning culture. The research is conducted at MI Al-Akbar Mosque in Surabaya. It employs a descriptive qualitative research methodology utilizing data collection techniques including interviews, observations, and documentation. Six research informants participated, including the madrasa head, curriculum coordinator, Cambridge primary coordinator, regular class teacher, CIP class teacher, and Islamic religious education subject teacher. Data analysis involves collecting, condensing, displaying data, and drawing conclusions/verifying data. The research findings demonstrate that Cambridge Primary was effectively and efficiently implemented under the provisions of the Al-Akbar National Mosque in Surabaya and Cambridge Assessment International Education (CAIE). The program spans grades 1 to 6, focusing on subjects such as science, mathematics, and English, with evaluations tailored to each level.